Biosynthesis of novel cannabigerolic acid derivatives by engineering the substrate specificity of aromatic prenyltransferase - Lee, Hoe-Suk; Park, Jisu; Kim, Taejung; Min, Huitae; Na, Seongsu; Park, Soon Young; Park, Young-Tae; Yeon, Young Joo; Ham, Jungyeob (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionCannabinoids possess significant therapeutic potential, but their natural chemical diversity derived from plant biosynthesis is limited. Efficient biotransformation processes are required to expand the range of accessible cannabinoids. This study aimed to enhance the selective biosynthesis of cannabigerolic acid (CBGA) and its derivatives with varying aliphatic chain lengths, which serve as key precursors to various cannabinoids.MethodsWe employed computational modeling and structure-guided mutagenesis to engineer the aromatic prenyltransferase NphB. Mutants were designed via in silico docking analyses to optimize substrate orientation and catalytic distance. The variants were expressed in E. coli, and their catalytic efficiencies were evaluated through in vivo whole-cell and in vitro enzymatic assays. Products were identified and quantified by UHPLC-MS.ResultsEngineered NphB variants exhibited significant improvements, with triple mutants achieving a 7-fold increase in CBGA production and a 4-fold increase in cannabigerovarinic acid production. Additionally, a single mutant also enhanced the synthesis of 3-geranyl orsellinic acid by 1.3-fold. Notably, novel enzymatic activity was identified that enabled the biosynthesis of 3-geranyl-2,4-dihydroxybenzoic acid. Structural analyses revealed that the mutations improved the spatial positioning of aromatic substrates relative to the co-substrate geranyl pyrophosphate.DiscussionThis study demonstrates the feasibility of enzyme design to tailor prenyltransferase specificity for the production of diverse CBGA derivatives. These findings lay the groundwork for the microbial production of novel cannabinoids and offer promising potential for the development of scalable biocatalytic systems for therapeutic and industrial applications.